Understanding flower-bud rot development caused by Pseudomonas syringae pv. actinidiae in green-fleshed kiwifruit - Kabir, M. Shahjahan; Parry, Bethan E.; Tyson, Joy L.; Beresford, Robert M. (New Zealand Plant Protection, 2019)
A greater understanding of the epidemiology of flower bud rot caused by Pseudomonas syringae pv. actinidiae (Psa) in New Zealand green-fleshed kiwifruit cultivars is required to develop successful disease-management strategies. This study sought evidence as to whether the source of Psa bacteria that causes flower bud infection is internal or external to the flower buds as they emerge in spring. Psa was detected using qPCR in asymptomatic flower buds of two green-fleshed cultivars during spring 2016 and 2017, between bud emergence and immediately before flower opening. Bacterial isolations were made from surface sterilised and non-sterilised buds. Asymptomatic and symptomatic buds were dissected and isolations made from each of the dissected flower parts over time. Significantly more Psa was detected from non-sterilised flower buds during the early stages of bud development compared with later stages. Bud dissections showed that Psa colonisation began in the outer flower parts and moved inwards and this coincided with the development of bud rot symptoms. This study supports a hypothesis that bud rot arises when buds are externally contaminated by Psa early in their development and subsequent infection moves into the inner parts of developing flowers, destroying tissue and causing bud death. Effective control must aim to prevent initial Psa contamination.